Gender-Related Persecution as a Basis for Refugee Status: The Emergence of an International Norm - Kuttner, Stephanie (Refuge: Canada’s Journal on Refugees, 1997)
In 1993, Canada was the first country to formally open its doors to refugees fleeing gender-related persecution. While the timing of Canada’s move may have been motivated by domestic politics, it was also tied to an international process through which the human rights of women and gender-related persecution had become politically relevant issues. This article investigates the emergence of an international norm accepting gender- related persecution as a basis for refugee status. It begins with an overview of developments on the matter in other jurisdictions and reveals the role Canada played by taking a first step. The article also reveals the process through which domestic, transnational and international actors converged to put the issue of gender-related persecution on the international agenda.